A inclusão escolar de estudantes surdocegos na perspectiva de professores do atendimento educacional especializado - Giza, Francieli (2023)
Specialized Educational Assistance (SEA) is a modality of Special Education existing in inclusive schools. Deafblind students, the target audience of this research, are served in the Multifunctional Resource Rooms - Deafness and Visual. In this context, the bilingual teacher identifies the demands in the area of deafblindness, and deafblind students can also receive monitoring through SEA. Given this, this research has as its central objective to analyze the main forms of communication and interaction of the deafblind person and how the teaching and learning process develops in the perspective of teachers of the SEA. The research is qualitative, descriptive, and exploratory. Its theoretical framework is the Historical-Cultural approach, based on the understanding that the person with disabilities learns and develops depending on the quality of mediation they receive, therefore, the deafblind person needs differentiated resources for this learning. The fieldwork was carried out through interviews with four bilingual teachers who work with deafblind students in the ESA of educational institutions in different municipalities linked to the Regional Center of Education (NRE), namely: Cascavel, Francisco Beltrão, and Toledo, all from the state of Paraná. After the discussions and analyses were undertaken, it can be concluded that the theme of deafblindness needs to be more dialogue, becoming the focus of more research, given that many deafblind students do not receive adequate education because they are not properly recognized. In addition, it is essential to continue investing in the initial and continuing training of professionals who work with these subjects, guaranteeing them access to inclusive and quality education.